Pharmacokinetics and safety of single doses of tabalumab in subjects with rheumatoid arthritis or systemic lupus erythematosus. (25th February 2016) - Witcher, Jennifer; Fleischmann, Roy; Chindalore, Vishala L.; Hansen, Ryan J.; Hu, Leijun; Radtke, David; Voelker, James; Gomez, Elisa; McColm, Juliet
Abstract : Aims: Two phase 1 studies evaluated the pharmacokinetics (PK), safety and biological activity of tabalumab, a human monoclonal antibody against B‐cell activating factor (BAFF), administered intravenously (i.v.) or subcutaneously (s.c.) in subjects with rheumatoid arthritis (RA) or systemic lupus erythematosus (SLE). Methods: In study A, subjects with RA ( n  = 23) or SLE ( n  = 6) received a single i.v. dose of tabalumab (RA 0.01, 0.04, 0.125, 0.5, 2.0, and 8.0 mg kg –1 and SLE 0.125 or 2.0 mg kg –1 ) or placebo. In study B, subjects with RA received a single tabalumab dose i.v. (10 mg) ( n  = 12) or s.c. (20 mg) ( n  = 12). Serum tabalumab and CD20+ B cells were evaluated and safety was assessed throughout both studies. Results: Tabalumab PK were non‐linear across the 0.01 to 8.0 mg kg –1 dose range. Clearance (CL) decreased from 2.9 to 0.1 l day –1 and terminal half‐life ( t 1/2 ) increased from about 1.6 to 25 days. Subjects with RA or SLE had similar PK. After s.c. dosing, tabalumab time to maximal concentration ( t max ) was 5.5 days. Absolute bioavailability ( F ) was approximately 62%. Following tabalumab dosing, CD20+ B cells transiently increased from baseline followed by a progressive decrease below baseline. Conclusion: A single tabalumab dose administered i.v. or s.c. was well tolerated and had non‐linear CL over the dose range investigated in subjects with RA and SLE. The non‐linearity likely reflects target‐mediated CL due to binding to BAFF. Tabalumab showed biological activity based on changes in peripheral CD20+ lymphocyte numbers in both subjects with RA and SLE.